Electrokinetic Performance on Dewatering in Soft Clay Subjected to Vertical Configurations of Electrode - Yubonchit, Somjai; Chinkulkijniwat, Avirut; Julvorawong, Mantana (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
To examine electrokinetic performance on dewatering and settlement in soft clay subjected to vertical configurations of electrode, this research conducted a series of experiments for two configurations of electrode. There were two configurations of electrode; 1) anode were placed at top and cathode placed at bottom boundaries namely as 1AT, and 2) two anodes were placed at top and bottom boundaries and cathode was placed at middle labeled as 2ATB. The results showed that greatest magnitudes of settlement and dewatering in soft clay for the both two configurations of electrode was shown in early stage of experiments. The 1AT yielded the settlement of 21.28 mm which was less than the settlement found in 2ATB test of about 20%. The settlement results were corresponded to dewatering in the soil sample in which the dewatering for 2ATB was greater than that for 1AT of about 10%. However, cracks in the soil sample were found in both the 1AT and the 2ATB. For the 1AT, the crack was appeared at top surface of the soil sample caused by downward dewatering from anode to cathode which was resulting in loss of water content nearby anode. While two anodes were placed at top and bottom boundaries of the soil sample for 2ATB, dewatering in both upward and downward directions from anodes to cathode placed at middle would generate cracks at top and bottom boundaries of the soil sample. The cracks due to reduction of water content during the experiment affects the efficiency of electrokinetic, including electric current and electrical resistance. It found that energy consumption used for 2ATB test was greater that for 1AT of about 40%. From the tested results, it can be conclude that electrokinetic technique is suited for any problem that requires smaller amount of dewatering within very short time period and...